If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x+12)=-49
We move all terms to the left:
6(x+12)-(-49)=0
We add all the numbers together, and all the variables
6(x+12)+49=0
We multiply parentheses
6x+72+49=0
We add all the numbers together, and all the variables
6x+121=0
We move all terms containing x to the left, all other terms to the right
6x=-121
x=-121/6
x=-20+1/6
| 6^3x-2=11 | | 3(c−9.07)=–5.01 | | (1)/(2)c+10=(5-7c)/(6) | | -2x+-0.5=x | | -2x+2(2x-3)=-4 | | 2/6k+80=3/6k+180 | | 9/45=x/70 | | (x+19)=(12x+8) | | 3p+18=5p+10 | | 1/4x+5/6=8/12 | | x/5+9=−2x= | | 2x+49=-8(-x-5 | | 4x+11=-59–6x | | x^2−2x−48=0 | | -2t=t-3t | | 8+9x=98 | | -2x-x+9=3x-9 | | –0.4x+4=–1.6 | | 6x-8=8+9x | | 15=|10-3x| | | 5p−10=5p | | 20(s-924)=580 | | 5d+9d=28 | | 8+9x=82 | | y/4+3=17 | | 8x+5=13x+14 | | x2+8=3x+36=180 | | 4y+8=6+2y | | 4=c/18-4 | | b-24=82 | | 1/4(4+x=4/3 | | 100*1.02^x=2*100 |